The relationship between the water regime and morphology of soils in the Weatherley catchment, northerly Eastern Cape - Van Huyssteen, Cornelius Wilhelm (University of the Free State, 2003)
The Weatherley catchment is situated close to Maclear in the northern Eastern Cape Province. Soil water contents have been measured regularly, as part of a long-term project, at 28 sites in the catchment for six years to quantify the soil water regime. For this study tEm of these sites were selected, described and analysed in detail to characterize the soil properties. This data was used to determine the relationship between soil water regime and soil profile morphology. A correlation was found to exist between mean annual duration of water saturation above 0.7 of porosity (ADs>o.7, days year") and other soil properties. CECsoil increases from 3.5 to 11.5 crnol, kg-1 , base saturation increases from 25 to 44 %, and the underlying unspecified material with signs of wetness or G horizons occur closer to the soil's surface as mean ADs>o.7 increases. Orthic A horizons that occur in seeps are wetter, with mean ADs>o.7 212 - 365 days year", than orthic A horizons that occur on ridges with mean ADs>o.7 of < 25 days year". The former have common and many Fe oxide mottles, whereas the latter lack clear mottling. ADs>o.7 data.shows that orthic A horizons overlying red apedal B, yellow-brown apedal B or neocutanic B horizons are well drained, while those overlying E, soft plinthic Band G horizons are wetter. It is proposed that orthic A horizons can be subdivided into wetness classes using the occurrence of mottles, as well as the nature of the underlying horizon. The Longlands (P201 and P207) and Westleigh (P204) soils, characterized by the occurrence of a soft plinthic B horizon, have intermediate mean ADs>o.7. They increase from 84 to 157 days year" in orthic A horizons, to 231 days year" in soft plinthic B horizons and 360 days year" in the underlying unspecified material with signs of wetness. The chromatic soils, including Pinedene (P202), Tukulu (P203) and Bloemdal (P210) soil forms, defined as having yellow-brown apedal B, neocutanic B or red apedal B horizons as the second horizon in the profiles respectively have the driest water regime of the soils studied. The A and B1 horizons have mean ADs>o.7 < 40 days year'", the B2 horizons 88 days year", and the underlying unspecified material with signs of wetness 130 to 350 days year" . Pooling the data from all the profiles studied produces the following mean ADs>o.7 for the different diagnostic horizons: G horizons = 324 ± 20 days year": unspecified material with signs of wetness = 243 ± 40 days year": E horizons = 163 ± 56 days year": soft plinthic B horizons = 148 ± 45 days year": orthic A horizons = 144 ± 40 days year'"; and chromatic (red apedal B, yellow-brown apedal Band neocutanic B) horizons = 88 ± 51 days year". There is an association between mean ADs>o.7 and other soil properties. For example clay content, CEC, basic cations and pH are highest in G horizons and lowest in chromatic horizons. CBD extractable Fe and Mn are found to be roughly twice as much in soft plinthic B, chromatic B and unspecified material with signs of wetness horizons compared to orthic A, E or G horizons. Digital soil horizon photographs were quantified and classified into diagnostic red, yellow-brown, grey and black colours, using the Red and Green values of RGBnotation in ArcView SpatialAnalyst. This methodology produced promising results, as proven by classification of photographed Munsell colour sheets. Colour classification of horizon photographs generally supports the field colour classification of these horizons using Munsell colour sheets. In general, the profiles described for this study are dominated by diagnostic grey and yellow-brown colours, with the exception of the Bloemdal (P210) which is diagnostic red.

Die Weatherley opvanggebied is naby Maclear in die Noordelike Oos-Kaapprovinsie geleë. As deel van 'n langtermyn projek is grondwaterinhoud gereeld vir ses jaar by 28 lokaliteite in die opvangebied gemeet om die grondwaterregime te kwantifiseer. Vir hierdie studie is tien van hierdie lokaliteite is geselekteer, in detail beskryf en geanaliseer om die grondeienskappe te karakteriseer. Hierdie data is gebruik om die verwantskap tussen grondwaterregime en grondmorfologie te bepaal. 'n Korrelasie is tussen jaarlikse duur van waterversadiging bo 0.7 van porositeit (ADs>o.7, dae [aar") en ander grondeienskappe gevind. KUKgrondneem toe van 3.4 na 11.5 crnol, kg-1 , basis versadiging neem toe van 25 % na 44 %, en die onderliggende ongespesifiseerde materiaal met tekens van natheid of G horisonte kom nader aan die grondoppervlak voor, soos ADs>o.7 toeneem. Ortiese A horisonte wat in vleie voorkom is natter (gemiddelde ADs>o.7 212 - 365 dae [aar'") as ortiese A horisonte wat op kruine (gemiddelde ADs>o.7 < 25 dae [aar'") voorkom. Eersgenoemde het volop en baie Fe oksied vlekke, terwyl laasgenoemde geen duidelike vlekke het nie. ADs>o.7 data dui daarop dat ortiese A horisonte watbo rooi apedale B, geelbruin apedale B of neokutaniese B horisonte voorkom goed gedreineer is, terwyl ortiese A horisonte wat op E, sagte plintiese B en G horisonte voorkom relatief nat is. Daar word voorgestel dat ortiese A horisonte in natheidsklasse onderverdeel kan word deur die voorkoms van vlekke en die aard van die onderliggende materiaal te gebruik. Die Longlands (P201 en P204) en Westleigh (P207) gronde, gekarakteriseer deur die voorkoms van sagte plintiese B horisonte, het intermediêre gemiddelde ADs>o.7. Dit neem toe van 84 tot 157 dae [aar" in ortiese A horisonte, na 231 dae [aar" in sagte plintiese B horisonte en 360 dae [aar" in die onderliggende ongespesifiseerde materiaal met tekens van natheid. Chromatiese gronde, wat die Pindene (P202), Tukulu (P203) en Bloemdal (P210) insluit en gedefinieer is deur die voorkoms van 'n neokutaniese B, geelbruin apedale B of rooi apedale B horison as die tweede horison in die profile onderskeidelik, het die droogste water regime van gronde wat bestudeer is. Die A en B1 horisonte het gemiddelde ADs>o.7 < 40 dae [aar'", die B2 horisonte 88 dae jaar" en die onderliggende materiaal met tekens van natheid 130 tot 350 dae [aar". Groepering van data van al die profiele lewer die volgende gemiddelde ADs>o.7 vir die verskillende diagnostiese horisonte: G horisonte = 324 ± 20 dae [aar": ongespesifiseerde materiaal met tekens van natheid = 243 ± 40 dae jaar'"; E horisonte = 163 ± 56 dae [aar": sagte plintiese B horisonte = 148 ± 45 dae [aar": ortiese A horisonte = 144 ± 40 dae [aar": en chromatiese (rooi apedale B, geelbruin apedale B en neokutaniese B) horisonte = 88 ± 51 dae jaar". Daar is 'n verwantskap tussen gemiddelde ADs>o.7 en ander grondeienskappe. Byvoorbeeld die klei inhoud, KUK, basiese katione en pH is hoogste in G horisonte en laagste in chromatiese horisonte. CBD ekstraheerbare Fe en Mn is ongeveer dubbeld in sagte plintiese B, chromatiese B en ongespesifiseerde materiaal met tekens van natheid as in ortiese A, E of G horisonte. Digitale grond horison foto's is in diagnostiese rooi, geelbruin, grys en swart kleure geklassifiseer en gekwantifiseer, deur die Rooi en Groen waardes van RGB notasie in ArcView SpatialAnalyst te gebruik. Die metode lewer belowende resultate, soos bewys deur die klassifikasie van foto's van Munsell kleurvelle. Kleurklassifikasie van horison foto's bevestig oor die algemeen veld kleurklassifikasie met behulp van Munsell kleur velle. Profiele in hierdie studie word oor die algemeen gedomineer deur diagnostiese grys en geelbruin kleure, met die uitsondering van P210 (Bloemdal) wat diagnosties rooi is.
Thesis (Ph.D. (Soil Science))--University of the Free State, 2003.
Keywords: Soil moisture -- South Africa -- Eastern Cape; Waterlogging (Soils) -- South Africa -- Eastern Cape; Soils -- Color -- South Africa -- Eastern Cape